An Intelligent Safety Warning and Alert System (ISWAS) for Automobile Vehicle - Chee, Fuei Pien; Angelo S. F; Asmahani Awang; Jedol Dayou; Jackson C.H.W (2018)
An estimated amount of nearly 1.24 million people dies every year from Road Traffic Accident. Despite the fact that most cars nowadays are equipped with automobile safety technology such as seat belts and airbags system, yet, their functionality is only limited for the prevention of further injuries after an accident. Due to the limitations of the existing automobile safety technology, a better and safer automobile design for prevention of pre-accident is therefore crucial. This project introduces a system namely Intelligent Safety Warning and Alert System (I-SWAS) using Arduino microcontroller as a based operation which offers a low-cost alternative in automobile safety technology for pre-accident prevention and hence reducing the Road Traffic Accident while providing corrective behavioral elements to the drivers driving ability.